Socio-behavioral correlates of pre-exposure prophylaxis use and correct adherence in men who have sex with men in West Africa - (:unkn) unknown (My University, 2022)
Background: Multiple barriers compromise pre-exposure prophylaxis (PrEP) engagement (i.e., use and adherence) in men who have sex with men (MSM). In low/middle-income countries, little is known about PrEP engagement in this population. In West Africa, the CohMSM-PrEP study was one of the rare interventions providing PrEP to MSM. We estimated PrEP use and correct adherence rates in CohMSM-PrEP, together with associated factors over time. METHODS: CohMSM-PrEP recruited MSM in four community-based clinics in Mali, Côte d'Ivoire, Burkina Faso, and Togo. Quarterly follow-up included collecting socio-behavioral data, and providing a comprehensive HIV prevention package, PrEP (daily or event-driven), and peer educator (PE)-led counselling. Using repeated measures, multivariate generalized estimating equations models were used to identify factors associated with self-reported i) PrEP use and ii) correct PrEP adherence during participants' most recent anal intercourse (defined as four pills/week for daily users and 2 + 1 + 1 for event-driven users).Results: Five hundred twenty participants were included with a median follow-up time of 12 months (IQR 6-21). Of the 2839 intercourses declared over the follow-up period, PrEP use was self-reported for 1996 (70%), and correct PrEP adherence for 1461 (73%) of the latter. PrEP use was higher in participants who also attended participating clinics outside of scheduled visits (adjusted odds ratio (aOR) [95% Confidence Interval, CI], p-value; 1.32[1.01-1.71], 0.040), and in those who practiced condomless anal sex (1.86[1.54-2.24], < 0.001). Correct adherence was higher in those who often contacted PE outside of scheduled visits (2.16[1.01-4.64], 0.047) and in participants who adopted receptive/versatile sexual positions with stable partners (1.36[1.03-1.81], 0.030). Instead, after an interaction effect between financial situation and regimen was tested, it was lower in event-driven users with a difficult/very diff
Keywords: African Research